Review on Various Issues and Design Topologies of Edge Coupled Coplanar Waveguide Filters - Kumar, Manoj; Gowri, Ravi (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*307.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932633);" role="presentation">In this paper, we put forward the litera<span dir="ltr" style="left: calc(var(--scale-factor)*227.21px); top: calc(var(--scale-factor)*307.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939865);" role="presentation">ture review related to filter <span dir="ltr" style="left: calc(var(--scale-factor)*337.87px); top: calc(var(--scale-factor)*307.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899446);" role="presentation">design issues and various design topologies to <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950487);" role="presentation">implement the practical edge coupled coplanar waveguide filters. <span dir="ltr" style="left: calc(var(--scale-factor)*347.83px); top: calc(var(--scale-factor)*321.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977958);" role="presentation">One of the main objectives of this survey <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950129);" role="presentation">paper to find out the comparison between various designs topologies on t<span dir="ltr" style="left: calc(var(--scale-factor)*379.15px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896132);" role="presentation">he basis <span dir="ltr" style="left: calc(var(--scale-factor)*416.23px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*428.47px); top: calc(var(--scale-factor)*334.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919593);" role="presentation">several parameters like <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*347.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957028);" role="presentation">providing flexibility to minimize analysis complexity, bandwidth and size reduction of edge coupled coplanar <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*360.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928759);" role="presentation">waveguide filters without loss of accuracy. Another objective is to provide the novel approach in order to help a <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*374.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906407);" role="presentation">researcher to find the suitable edge coupled coplanar waveguide filter design topologies.